The genetic and epigenetic regulation of CD55 and its pathway analysis in colon cancer - Liu, Jiawei; Fu, Ning; Yang, Zhenbang; Li, Ang; Wu, Hongjiao; Jin, Ye; Song, Qinqin; Ji, Shanshan; Xu, Hongxue; Zhang, Zhi; Zhang, Xuemei (Frontiers in Immunology, 2023)
Background: CD55 played an important role in the development of colon cancer. This study aims to evaluate the expression of CD55 in colon cancer and discover how it was regulated by transcriptional factor and miRNA. Methods: The expression of CD55 was explored by TIMER2.0, UALCAN, and HPA databases. TRANSFAC and Contra v3 were used to predict the potential binding sits of transcription factors in the CD55 promoter. TargetScan and Starbase v2.0 were used to predict potential binding ability of miRNAs to the 3’ untranslated region (3’UTR) of CD55. SurvivalMeth was used to explore the differentially methylated sites in CD55 promoter. Western Blot was used to detect the expression of TFCP2 and CD55. Dual-luciferase reporter assay and ChIP assay were performed to determine the targeting relationship of TFCP2, NF-κB, or miR-27a-3p with CD55. CD55 related genes was explored by constructing a protein-protein interaction (PPI) network and was performed pathway analysis by GO and KEGG. Results: CD55 was highly expressed in colon cancer tissues. The mRNA and protein expression level of TFCP2 were reduced by si-TFCP2. NF-κB mRNA were obviously reduced by NF-κB inhibitor and increased by NF-κB activator. CD55 protein was also inhibited by miR-27a-3p. Dual luciferase reporter assays showed that after knocking down TFCP2 or inhibiting NF-κB, the promoter activity of CD55 was decreased by 21% and 70%, respectively; after activating NF-κB, the promoter activity of CD55 increased by 2.3 times. As TFCP2 or NF-κB binding site was mutated, the transcriptional activity of CD55 was significantly decreased. ChIP assay showed that TFCP2 and NF-κB combined to the promoter of CD55. The luciferase activity of CD55 3’UTR decreased after co-transfected with miR-27a-3p mimics and increased by miR-27a-3p antagomir. As miR-27a-3p binding site was mutated, we didn’t find any significant effect of miR-27a-3p on reporter activity. PPI network assay revealed a set of CD55-related genes, which including CFP, CFB, C4A, C4B, et al. GO and KEGG analysis revealed that the target genes occurred more frequently in immune-related pathways. Conclusion: Our results indicated that CD55 was regulated by TFCP2, NF-κB, miR-27a-3p and several immune-related genes, which in turn affects colon cancer.